THE EFFECT OF UNDERHAND PASS TRAINING USING WALL MEDIA AND PAIRED METHODS ON UNDERHAND PASSING SKILLS IN VOLLEYBALL AMONG EXTRACURRICULAR STUDENTS AT SMP TAHFIDZUL QUR’AN AD-DIIN MANGLI KUWARASAN - Mokhamad Farid Muazin; Alfiah rizqi Azizah (Ikatan Dosen Menulis, 2026)
This study aimed to analyze the effect of underhand pass training using wall media and paired methods on underhand passing skills in volleyball among extracurricular students at SMP Tahfidzul Qur’an Ad-Diin Mangli Kuwarasan. This study employed a quantitative approach with a quasi-experimental design (one group pretest-posttest design). The research sample consisted of 20 students selected through purposive sampling. The instrument used was a volleyball underhand passing skill test adapted from Herdaphasa et al. (2023) and Effendy et al. (2020). The training intervention was conducted for 6 weeks with a frequency of 3 times per week, each session lasting 60 minutes. Data were analyzed using paired t-test with a significance level of α = 0.05. The results showed that: (1) there was a significant increase in underhand passing skills after training using wall media (p < 0.05); (2) there was a significant increase in underhand passing skills after training using paired methods (p < 0.05); (3) the combination of wall media and paired method training significantly influenced the improvement of students’ volleyball underhand passing skills. The conclusion of this study is that underhand pass training using wall media and paired methods effectively improves volleyball underhand passing skills among extracurricular students.